CRh‐Catalyzed Hydroformylation of Divinylglycol: An Effective Way to Access 2, 7‐Dioxadecalin‐3, 8‐diol. Issue 27 (2nd July 2019) - Bricout, Hervé; Vanbésien, Théodore; Wei, Muh‐Mei; Billamboz, Muriel; Len, Christophe; Monflier, Eric; Hapiot, Frédéric
Abstract : Obtained from glycerol, divinylglycol (DVG) is a promising bio‐based building block. Upon hydroformylation of DVG, a very complex mixture of different products is obtained. Unexpectedly, the addition of chloroform at 0 °C on this mixture provokes the selective precipitation of 2, 7‐dioxadecalin‐3, 8‐diol, an interesting bicyclic bis‐hemiacetal. Abstract : Upon hydroformylation of divinylglycol, a very complex mixture of different products is obtained. Addition of chloroform provokes the selective precipitation of 2, 7‐dioxadecalin‐3, 8‐diol, an interesting bicyclic bis‐hemiacetal.